Sense of Parenting Efficacy, Perceived Family Interactions, and Parenting Stress Among Mothers of Children With Autistic Spectrum Disorders - Chen, Yirong; Cheng, Tianyi; Lv, Fangyan (Frontiers in Psychology, 2022)
This study examined the relationship between maternal sense of parenting efficacy and parental stress in children with autism and the moderating effect of family interaction. A total of 263 mothers of children with autism were investigated with the Parenting Ability Scale, Family Interaction Scale (FIS), and Parental Stress Scale. The results showed that (1) maternal sense of parenting efficacy significantly predicted parental stress in children with autism; and (2) family interaction significantly moderated the relationship between maternal sense of parenting efficacy and parental stress in children with autism, that is, when family interaction was lower than −1.54 standard deviation (SD), the sense of parenting efficacy did not significantly predict parental stress. When family interaction was higher than −1.54 SD, parenting efficacy had a significant negative predictive effect on parenting stress.